2008
DOI: 10.1002/bjs.5913
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of endothelial progenitor cells into the circulation in burned patients

Abstract: Thermal injury induced a rapid rise in EPCs that was proportional to the extent of the burn and significantly correlated with levels of angiogenic cytokines. Such cytokines may be used to stimulate EPCs as a future therapeutic target in burned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 30 publications
(38 reference statements)
5
56
0
Order By: Relevance
“…Both VEGF and G-CSF are cytokines implicated in the acute mobilization of endothelial progenitor cells by VDAs (13). In our study, CEC and CEPC numbers were so low (on average less than 50 cells/mL) that these cell populations were not quantifiable with confidence, although the same standardized method detected changes in burns patients (34,35), patients in a phase I trial of antiangiogenic therapy (36) and patients on OXi4503, another VDA (13,35). However, the numbers of the overall bone marrow progenitor population CD45 À /dim CD34 þ or CD133 þ cell populations did increase significantly following treatment and the CEC or CEPC populations form a small part of these larger cell populations.…”
Section: Discussionmentioning
confidence: 57%
“…Both VEGF and G-CSF are cytokines implicated in the acute mobilization of endothelial progenitor cells by VDAs (13). In our study, CEC and CEPC numbers were so low (on average less than 50 cells/mL) that these cell populations were not quantifiable with confidence, although the same standardized method detected changes in burns patients (34,35), patients in a phase I trial of antiangiogenic therapy (36) and patients on OXi4503, another VDA (13,35). However, the numbers of the overall bone marrow progenitor population CD45 À /dim CD34 þ or CD133 þ cell populations did increase significantly following treatment and the CEC or CEPC populations form a small part of these larger cell populations.…”
Section: Discussionmentioning
confidence: 57%
“…Our approach to examining the effects of AMD3100 in a complex in vitro microenvironmental model of neovascularization may prove significant for understanding the mechanisms of action of this and other drugs and associated molecules in promoting or inhibiting revascularization and for more clearly defining the experimental approach to testing or assessing the effects of such drugs in vitro and subsequently in vivo. Understanding such mechanisms as those exemplified here with CXCL12 in new blood vessel formation has translational implications that include inhibition of tumor progression and promotion of tissue repair and regeneration as diverse as peripheral arterial disease and ischemic injury, burn injury, neurodegenerative disease, and hematological regeneration [5][6][7]11,18,22,[56][57][58][59][60].…”
Section: Fig 6 Cd31 Blocks Integration Of Exogenous Huvecs Into Immmentioning
confidence: 99%
“…These include hematopoietic stem/ progenitor cell (HSC/HPC) trafficking, immune surveillance, blood vessel, cardiac and central nervous system formation during development, revascularization at sites of tissue injury, and the initiation and metastatic spread of tumors [1][2][3][4][5][6][7][8][9]. CXCL12 plasma levels are rapidly elevated in response to tissue damage, with increased CXCL12 concentrations correlating with the severity of injury, increased vascular endothelial growth factor (VEGF) plasma levels, and the associated rapid mobilization of proangiogenic cells into the circulation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have indicated that mesenchymal stem cell-associated CD34 -/VE-cadherin -/AC133 + /Flk-1 + multipotent adult progenitor cells (MAPCs) may be converted to CD34 + /VE-cadherin -/AC133 -/Flk + angioblasts by the action of VEGF and that these cells may be further differentiated into mature endothelial cells (23,29,30) and become involved in tumor angiogenesis and wound healing. The cell surface markers of EPCs have not been fully elucidated and there continues to be large variances in the reported quantities of EPCs present in the circulation and uncertainty regarding the best enrichment and isolation methods (31,32). Thus, the specific phenotype that may distinguish EPCs from hematopoietic cells or mature endothelial cells still requires further exploration, which provides the motivation for continued progression in the method described in the present study.…”
Section: Discussionmentioning
confidence: 99%